If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 7) + -6 = -20 + 6x Reorder the terms: -1(7 + x) + -6 = -20 + 6x (7 * -1 + x * -1) + -6 = -20 + 6x (-7 + -1x) + -6 = -20 + 6x Reorder the terms: -7 + -6 + -1x = -20 + 6x Combine like terms: -7 + -6 = -13 -13 + -1x = -20 + 6x Solving -13 + -1x = -20 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -13 + -1x + -6x = -20 + 6x + -6x Combine like terms: -1x + -6x = -7x -13 + -7x = -20 + 6x + -6x Combine like terms: 6x + -6x = 0 -13 + -7x = -20 + 0 -13 + -7x = -20 Add '13' to each side of the equation. -13 + 13 + -7x = -20 + 13 Combine like terms: -13 + 13 = 0 0 + -7x = -20 + 13 -7x = -20 + 13 Combine like terms: -20 + 13 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| N^2+16=-8n | | 3[4x-5(y-2)]= | | -3x-1=x-17 | | -5=9+4 | | X+4(x+2)=12 | | -2(9+4s)=34 | | 5a^2= | | 3a+12=6a+7 | | 4x^3-6x-6=0 | | -7(1-5h)=21 | | 3x+2y+2x+5z+7y+2z= | | 5x+13y=11 | | 3x(4)=180 | | 4.5(6.2)=n | | 3(3y-3)-2(y-6)= | | m^2-3m+5=0 | | 35-6x=-(1-3x) | | 60+x+68+68=180 | | 48b+24= | | 4.5(6.2)= | | -76+x=-33 | | 10x-9.4=2x+12.8 | | 4x^3-48x^2+8=0 | | R(x)=8x^2+12x+4 | | (2/5)÷(10/9) | | 0.45/4.2=p/15 | | 10x-16=7x+15 | | 5x^2+3x-27= | | 3(5x+-6)+9=4(3x+12)+3 | | 5+3=35 | | -64x^3-72x^2=-486x | | 2lnx-ln(2x-9)=ln(7x)-ln(x-2) |